Structural adjustment in Central America: the case of Costa Rica - Hansen-Kuhn, Karen (Development GAP WashingtonUS, 1993)
Examines the effects on structural adjustment programmes in Central America with particular reference to Costa Rica. Concludes that these policies have not led Costa Rica out of economic crises and toward stable equitable development. Rather they have led the country into a series of new economic crises marked by growing disparities in wealth and income and extensive environmental damage.